Intravenous immunoglobulin in the management of severe early onset red blood cell alloimmunisation. (13th September 2022) - Vlachodimitropoulou, Evangelia; Lo, Tsz Kin; Bambao, Clarissa; Denomme, Greg; Seaward, Gareth R.; Windrim, Rory; Tessier, Francine; Kelly, Edmond; Van Mieghem, Tim; Ryan, Greg
Summary: Our objective was to assess the effect of maternal intravenous immunoglobulin (IVIG) administration for severe red blood cell (RBC) alloimmunisation on fetal outcomes. This is a case–control study. Women with a history of severe early onset alloimmunisation resulting in fetal loss in a previous pregnancy and high anti‐D or anti‐K antibody titres received IVIG in a subsequent pregnancy. We assessed gestational age at first transfusion and fetal outcomes in the subsequent pregnancy and compared these with the outcomes in the previous pregnancy. The most responsible antibody was anti‐D in 17 women and anti‐K in two others, whilst seven had more than one antibody. In all, 19 women received IVIG in 22 pregnancies, two of which did not even need an intrauterine transfusion (IUT). For previous early losses despite transfusion, IVIG was associated with a relative increase in fetal haemoglobin between treated and untreated pregnancies of 36.5 g/L (95% confidence interval 19.8–53.2, p = 0.0013) and improved perinatal survival (eight of eight vs. none of six, p = 0.001). For previous losses at <20 weeks, it enabled first transfusion deferral in subsequent pregnancies to at least 19.9 weeks (mean 23.2 weeks). Overall, IVIG decreases the severity of haemolytic disease of the fetus and newborn and allows deferral of the first IUT to a safer gestation in severe early‐onset RBC alloimmunisation and rarely may even avoid the need for IUT entirely.